Reviews of environmental contamination and toxicology volume 210 - Whitacre, David M.; SpringerLink (Online service). (New York Springer, 2011)
CONTENTS Foreword Preface Attenuation of Chromium Toxicity by Bioremediation Technology by Monalisa Mohanty and H. Kumar Patra The Effects of Radionuclides on Animal Behaviour by Beatrice Gagnaire, Christelle Adam-Guillermin, Alexandre Bouron, and Philippe Lestaevel Illicit Drugs: Contaminants in the Environment and Utility in Forensic Epidemiology by Christian Daughton Index.
Foreword -- Preface -- Attenuation of Chromium Toxicity by Bioremediation Technology by Monalisa Mohanty and H. Kumar Patra -- The Effects of Radionuclides on Animal Behaviour by Beatrice Gagnaire, Christelle Adam-Guillermin, Alexandre Bouron, and Philippe Lestaevel -- Illicit Drugs: Contaminants in the Environment and Utility in Forensic Epidemiology by Christian Daughton. Index.
Electronic reproduction.
Keywords: Pollution -- Environmental aspects; Environmental toxicology; Environmental Studies; Electronic books